Jeongeuplla avenae gen. nov., sp. nov., a novel β-carotene-producing bacterium that alleviates salinity stress in Arabidopsis - Jiang, Lingmin; Peng, Yuxin; Kim, Ki-Hyun; Jeon, Doeun; Choe, Hanna; Han, Ah-Reum; Kim, Cha Young; Lee, Jiyoung (Frontiers in Microbiology, 2023)
A novel endophytic bacterium, designated DY-R2A-6T, was isolated from oat (Avena sativa L.) seeds and found to produces β-carotene. Phylogenetic analysis based on 16S rRNA gene sequences revealed that strain DY-R2A-6T had 96.3% similarity with Jiella aquimaris LZB041T, 96.0% similarity with Aurantimonas aggregate R14M6T and Aureimonas frigidaquae JCM 14755T, and less than 95.8% similarity with other genera in the family Aurantimonadaceae. The complete genome of strain DY-R2A-6T comprised 5,929,370 base pairs, consisting of one full chromosome (5,909,198 bp) and one plasmid (20,172 bp), with a G+C content was 69.1%. The overall genome-related index (OGRI), including digital DNA–DNA hybridization (<20.5%), ANI (<79.2%), and AAI (<64.2%) values, all fell below the thresholds set for novel genera. The major cellular fatty acids (>10%) of strain DY-R2A-6T were C16:0, C19:0 cyclo ω8c, and summed feature 8 (C18:1ω7c and/or C18:1ω6c). Ubiquinone-10 was the main respiratory quinone. We identified the gene cluster responsible for carotenoid biosynthesis in the genome and found that the pink-pigment produced by strain DY-R2A-6T is β-carotene. In experiment with Arabidopsis seedlings, co-cultivation with strain DY-R2A-6T led to a 1.4-fold increase in plant biomass and chlorophyll content under salt stress conditions, demonstrating its capacity to enhance salt stress tolerance in plants. Moreover, external application of β-carotene to Arabidopsis seedlings under salt stress conditions also mitigated the stress significantly. Based on these findings, strain DY-R2A-6T is proposed to represent a novel genus and species in the family Aurantimonadaceae, named Jeongeuplla avenae gen. nov., sp. nov. The type strain is DY-R2A-6T (= KCTC 82985T = GDMCC 1.3014T). This study not only identified a new taxon but also utilized genome analysis to predict and confirm the production of β-carotene by strain DY-R2A-6T. It also demonstrated the ability of this strain to enhance salt stress tolerance in plants, suggesting potential application in agriculture to mitigate environmental stress in crops.